The Application of Blended Learning Model to Improve Student Learning Outcomes in Parts of the Body Material for Grade V Students During the Pandemic - Atika Meliyana; Muhammad Azka Maulana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
The aim of this study was to determine student learning outcomes on vocabulary mastery inmaterial parts of the body by applying blended learning model. This study used a quantitative method of independent sample t test with an experimental design. The population in this study amounted to 24 students in two groups, namely the experimental group which was treated with the learning model blended learning and the control group was given thetreatment face-to-face learning. The data used in this study came from the results of the pre-test and post-test, then analyzed by t-test. After the research data was collected and analyzed, the results showed that compared to the control group, the students in the experimental group had a significantly better understanding. This showed that the use of learning methods blended learning can effectively improve student learning outcomes towards mastery ofvocabulary parts of the body. Keywords: Learning outcomes; blended learning; parts of the body